Lateral Horizontal Head Position Approach for the Lateral and Anterior Third Ventricles: A Subependymoma Clinical Case and Literature Review - Doğu, Hüseyin; Akdemir, Hidayet; Çetin, Sırma (Asian Journal of Neurosurgery, 2022)
Subependymomas are benign, slow-growing, noninvasive solitary lesions of World Health Organization Grade I cerebral ependymal origin that are rare compared with other types of ependymomas. Anterior third ventricle subependymomas are usually detected during autopsies in cases of sudden death due to acute or intermittent obstruction of the cerebrospinal fluid passage. Different surgical approaches are used for these cerebral lateral and third ventricular lesions. Serious complications can occur, either because of brain edema and acute intracranial pressure due to the lesion itself or the chosen head position and continuous use of brain retractors during the surgical procedure.In this case report, we trust that the surgical principles we applied with the aid of two cotton pads, gravity assist, and lateral horizontal head position, and without continuous use of brain retractors in the third ventricular lesion in the transcallosal interhemispheric approach are safe and secure in preventing perioperative brain edema or early postoperative neurological complications.
Keywords: third ventricle; transcallosal interhemispheric; subependymoma